Wycena złożonych wartości niematerialnych w spółce internetowej na przykładzie Interia.pl - Góralski, Bartosz (Practical Valuation of Compound Intangible Assets in Internet Companies Based on Interia.pl, 2007)
Intangible and legal assets change the way in which economic entities do business, deal with employees, design their projects, sell services and talk to customers. These are long term changes which still are and will have huge significance for the strategy and reputation of enterprises, for short and long term decisions, for the communications and revealing of information and for government policy which shapes business circle. Value sources change and consequently the same happens to the way of management. Therefore the tools which can support managers in taking decision become important helping them in the estimation of the degree of strategic realization, the coordination of its realization and communications inside an enterprise. The aim of the article is a practical presentation of one of leading methods of complex intangible assets evaluation as an important tool in an estimation of an enterprise both for its owners and external stakeholders.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 174-186